Analysis of Parameterization Value Reduction of Soft Sets and its Algorithm - Mohammed, Mohammed Adam Taheir; Wan Maseri, Wan Mohd; Ruzaini, Abdullah Arshah; Mungad, M.; Sutoyo, Edi; Chiroma, Haruna (Penerbit UMP, 2016)
In this paper, the parameterization value reduction of soft sets and its algorithm in decision making are studied and described. It is based on parameterization reduction of soft sets. The purpose of this study is to investigate the inherited disadvantages of parameterization reduction of soft sets and its algorithm. The algorithms presented in this study attempt to reduce the value of least parameters from soft set. Through the analysis, two techniques have been described. Through this study, it is found that parameterization reduction of soft sets and its algorithm has yielded a different and inconsistency in suboptimal result.